The Relationship Between Quality of Life and Job Satisfaction in Autistic Workers - D. Hedley; S.M. Bury; J.R. Spoor (Moscow State University of Psychology and Education, 2020)
The current research sought to understand the relationship between job satisfaction and quality of life in employed individuals with Autism Spectrum Disorder (ASD). The research focuses on participants involved in a supported employment program for individuals with ASD, the DXC Technology Dandelion Program. We examined the sustained impact of participating in the supported employment program on quality of life and job satisfaction, via a longitudinal survey of the employees with ASD. Quality of life was assessed with the World Health Organization Quality of Life Brief, and intrinsic and extrinsic job satisfaction were assessed with the Minnesota Satisfaction Questionnaire (Short Form). Results indicated small but statistically non-significant (using an adjusted significance level of .001) changes in both quality of life and job satisfaction across a 12-month period. Results are discussed in terms of how to further improve the employment program and support employees with ASD.